Hubungan Karakteristik Individu dan Komunikasi Interpersonal dengan Stres Kerja pada Petugas Penjagaan (Sipir) di Lembaga Pemasyarakatan (Lapas) Klas IIA Wanita Semarang - Benedicta Sonya Ajeng Lestari; Ida Wahyuni; Ekawati Ekawati (Jurnal Kesehatan Masyarakat (Undip), 2017)
Each profession has a different pressure in the work , which in turn creates a level of job stress itself. One profession that can lead to job stress is guarding officer ( warden ) Women's prison in prisons . Warden on duty to maintain and foster the offenders the amount that should have been 186 but overall there are 269 inmates were prisoners and detainees is a woman with the characteristics (age and time served ) and different properties , thus allowing the emergence of job stress on the warden .The purpose of this research is to know the relation of characteristics of individual and interpersonal communication with work stres on the warden at correctional institutions (Lapas) Klas IIA Women Semarang.This researchwas anexplanatory research usedcross sectional approach. The sample inthis study were 30 warders.Chi Square was used to analyse the data.The results was used fisher’s exact test, there was a significant relationship between agewithwork stress(p-value = 0,003), there was a significant relationship between gender with work stress (p-value = 0,025), there was a significant relationship between wroking period with work stress (p-value = 0,002). However, there was no significant relationship between interpersonal communication withwork stress(p-value=1,000).It is recommended that the lapas should have a fitness program ( sports such as morning exercise) minumal regular basis once a week is required for the guards.